Evaluating the Triple Elimination Screening Program for Pregnant Women in Rokan Hilir District, Indonesia - Azzah Rawani; Riauni Syaputri; Budi Hartono (LPPM Universitas Harapan Bangsa, 2024)
The Triple Elimination program aims to prevent mother-to-child transmission of HIV, hepatitis B, and syphilis during pregnancy. This qualitative phenomenological study evaluated the implementation of the Triple Elimination program among pregnant women at the Rokan Hilir District Health Office in Indonesia. Five informants were purposively selected for in-depth interviews and document reviews. Data were analyzed using fishbone and SWOT analyses. Major barriers included limited knowledge and motivation among pregnant women due in part to inadequate midwife competencies in conducting screenings, insufficient health promotion infrastructure and activities, budget constraints, limited involvement of community stakeholders, and lack of supportive policies. Recommendations encompass enhancing midwife competencies, garnering policymaker support, optimizing community health cadres' roles, employing mobile health education strategies, and fostering partnerships through a Pentahelix approach. This streamlined abstract concisely summarizes the key aspects of the study including aims, methods, findings, and conclusions in clear language appropriate for an international audience